Applicability of the Calcaneal Apophysis Ossification Staging System to the Modern Pediatric Population. Issue 1 (January 2019) - Li, Samuel Q.; Nicholson, Allen D.; Cooperman, Daniel R.; Liu, Raymond W.
Abstract : Background: The calcaneal apophysis ossification staging system is a novel method for assessing skeletal maturity. However, it was created using the same historic patient population that was used to create the Greulich and Pyle atlas of the hand and wrist, predominantly white children. It is unclear if the calcaneal apophysis ossification staging system is still applicable to the modern pediatric population and to children of other races. Methods: We retrospectively studied 1327 benign lateral foot x-rays from modern white and black children. Calcaneal stage was determined and age, race, and sex were collected for each patient. A 2-tailed Student t test was used to compare between cohorts the differences in age for each calcaneal stage. Results: Mean age was 11.55±4.39 years. Modern white females graded as stage 3 and 4 were significantly delayed in their bone age (stage 3 P <0.002; stage 4 P <0.003) when compared with their historic counterparts. Skeletal maturity was consistent between modern and historic white males for stages 1 to 4. Modern black females graded as stage 1 to 4 were significantly advanced in their skeletal age when compared with modern white females (stage 1 P <0.038; stage 2 P <0.005; stage 3 P <0.002; stage 4 P <0.002). Modern black males graded as stages 1, 3, and 4 were also significantly advanced in their bone age when compared with their modern white counterparts (stage 1 P <0.003; stage 3 P <0.012; stage 4 P <0.029). Conclusions: Modern white females mature more slowly in the later stages when compared with their historic counterparts. No significant difference is seen between modern and historic white males. Modern black females and males were skeletally advanced compared with modern white females and males. We have shown that the calcaneal ossification staging system can be used to assess for skeletal maturity in the modern pediatric population with only mild corrections for white females and more significant adjustments for black females and males. Level of Evidence: Level III—retrospective chart review.